Hubungan Tingkat Pengetahuan Pasien Hemodialisa terhadap Kemampuan Perawatan Cimino secara Mandiri di Rumah Sakit Sentra Medika Cikarang - Murniati, Marbun; Umar, Wifadli; P, Padaallah A (Universitas Pahlawan Tuanku Tambusai, 2025)
End-stage Chronic Kidney Disease (CKD) constitutes a major global health concern. Complications in end-stage chronic kidney disease patients undergoing hemodialysis with a Cimino fistula can be mitigated with self-care behaviours. Behaviour (self-care) is defined as all efforts undertaken by end-stage CKD patients to preserve and enhance the health and functionality of the Cimino fistula during hemodialysis. This must be predicated on the patient's understanding of independently administered Cimino therapy. This study seeks to ascertain the correlation between the knowledge level of hemodialysis patients and their capacity for independent care of the Cimino fistula at Sentra Medika Cikarang Hospital. This research employs a quantitative analytical methodology utilizing a cross-sectional design. The sample for this study was determined using the Slovin formula, comprising a total of 102 respondents with renal failure receiving hemodialysis. The analysis employed univariate and bivariate methods utilizing the chi-square test. The results indicated a significant p-value of 0.000 (p < α). This study concludes that a correlation exists between the knowledge level of hemodialysis patients and their capacity for independent management of the Cimino fistula at Sentra Medika Cikarang Hospital.